Income Inequality measurement in Pakistan and its four provinces by Lorenz curve - Amir, Hina; Bilal, Kanwal (Journal of Asian Scientific Research, 2011)
The purpose of this research is to measure the income inequality firstly in four Provinces of Pakistan individually and eventually in the overall country. There is inequality among the income of people who constitute the nation; there is also inequality among the per capita income of different provinces. Overall inequality in Pakistan appears to be almost exclusively due to inequalities within provinces. Cross section data taken from Household economic survey (HIES) 1998-1999 was used for this purpose. Most appropriate method Lorenz Curve was used to measure income inequality between the provinces of Pakistan. Lorenz curve shows a quantitative relationship between the percentage of income recipients and the percentage of total income. After using the data of Average monthly income and number of sampled household, the column of total income (TY),total population(TP)and per capita income(PCY) Same population, income, population share (PS),income share(YS),cumulative population share percentage(CPS%)and cumulative income share percentage(CYS%)were obtained. Finally the tables which contained the values of CPS% and CYS% were used to draw the Lorenz curve which illustrated the situation of income inequality in four provinces (Punjab, Sindh, Khyber Pakhtunkhua, Baluchistan) of Pakistan. The higher the distance of Lorenz curve from perfect equality line shows the more inequality and lower the distance of Lorenz curve from perfect equality line shows less inequality. In this research Lorenz curve of one province of Pakistan e.g. Baluchistan is showing low distance from the perfect equality line, so the findings of this research paper is the income inequality is less in one province like Baluchistan because its curve is near to the 45 degree of perfect equality line than other provinces.